Implementation of Indoor Positioning System for Monitoring Geriatric Syndrome Patients Based on Bluetooth Low Energy - Nandika, Reza; Hidayat, Anton; Herizon; Nasution, Anggara; Putra, Andreansyah (Politeknik Negeri Padang, 2024)
Health issues commonly faced by the elderly include geriatric syndromes. The impact of these syndromes on older adults can lead to instability (disruption of balance, making them prone to falls) and intellectual impairment. Because of these concerns, monitoring is essential for individuals experiencing geriatric syndromes to prevent symptoms from worsening due to falls. As technology advances, object tracking systems using Global Positioning System (GPS) have developed significantly. However, GPS tracking systems are primarily suitable for outdoor tracking. Thus, there is a need for a method capable of detecting individuals with geriatric syndrome indoors and providing alerts if they fall. This study proposes a multi-room monitoring system for patients with geriatric syndrome to mitigate the adverse effects of falls by implementing an Indoor Positioning System (IPS) that utilizes Bluetooth Low Energy (BLE) technology and gyroscope sensors for fall detection. The proposed IPS employs BLE technology using the trilateration method. The ESP32 module is selected as the reference point for scanning BLE signals, measuring signal strength (RSSI), and transmitting data to a server for further processing via the Message Queuing Telemetry Transport (MQTT) protocol. The result of the test carried out during indoor conditions showed an average deviation in the x-cordinate of 0.28 meters and y-cordinate of 0.27 meters from the patients actual location.